2023
DOI: 10.1021/acs.nanolett.3c01769
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Organic Phosphonate Additive Induced Stable and Efficient Perovskite Solar Cells with Efficiency over 24% Enabled by Synergetic Crystallization Promotion and Defect Passivation

Caidong Cheng,
Yiguo Yao,
Lei Li
et al.

Abstract: Defect passivation is crucial to enhancing the performance of perovskite solar cells (PSCs). In this study, we successfully synthesized a novel organic compound named DPPO, which consists of a double phosphonate group. Subsequently, we incorporated DPPO into a perovskite solution. The presence of a PO group interacting with undercoordinated Pb2+ yielded a perovskite film of superior crystallinity, greater crystal orientation, and smoother surface. Additionally, the addition of DPPO can passivate defect states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 68 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…In addition, Yang et al showed that halide segregation was suppressed because of incorporating tri(heptafluorophenyl)phosphine (TPFP) containing a P=O group and three connected F atoms with strong electronegativity into perovskite films (Figure 8d) [119]. Cheng et al synthesized DPPO, with two phosphoric acid groups, and found that uncoordinated Pb 2+ defects in perovskite films were passivated due to the presence of a P=O group [124]. Furthermore, the alignment of the upper levels of the perovskite was adjusted by introducing DPPO into devices, and carrier extraction was improved, leading to reduced non-radiative recombination at the interface.…”
Section: Lewis Basementioning
confidence: 99%
“…In addition, Yang et al showed that halide segregation was suppressed because of incorporating tri(heptafluorophenyl)phosphine (TPFP) containing a P=O group and three connected F atoms with strong electronegativity into perovskite films (Figure 8d) [119]. Cheng et al synthesized DPPO, with two phosphoric acid groups, and found that uncoordinated Pb 2+ defects in perovskite films were passivated due to the presence of a P=O group [124]. Furthermore, the alignment of the upper levels of the perovskite was adjusted by introducing DPPO into devices, and carrier extraction was improved, leading to reduced non-radiative recombination at the interface.…”
Section: Lewis Basementioning
confidence: 99%
“…In general, the low-temperature solution preparation process of the perovskite active layer makes it well-compatible with other functional layers and substrates, which endows the PSCs with diverse device architectures and flexible application situations . Nevertheless, the high-density defect states and weak binding generated during this process diminish the resistance to moisture and cause significant energy loss, which is unfavorable to the long-term operation stability of PSCs. , To solve these problems, many effective additives have been developed to passivate various defects and improve device stability. Zheng et al used quaternary ammonium halides to simultaneously passivate positive and negative charge defects in mixed perovskite to achieve high-performance PSCs with an open-circuit-voltage deficit of only 0.35 V . Kong et al obtained high-quality perovskite films by adding 4-chlorophenyltrifluoroborate potassium salt, which mainly benefited from the synergistic effect of potassium ions and anionic groups .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have recently attracted significant research interest due to their tunable bandgap, high optical absorption, and impressive power conversion efficiency (PCE). Single-junction PSCs have already surpassed PCE of 25%. , While inverted PSCs still lag behind their regular single-junction counterparts in terms of PCE, there has been substantial growth in the past three years, primarily due to the development monolayers of carbazole-based self-assembled compounds for use as hole transport layers (HTLs) or hole-selective layers (HSLs) at the anode contact in PSCs. Regarding these outstanding inverted PSCs, rapid advancements in charge transport layers (CTLs) and their interfacial engineering, , along with passivation strategies, have enabled the realization of high-performance and ambient-stable perovskite-based devices. Nevertheless, defects frequently appear at the interface between the CTL and the perovskite layer, leading to nonradiative recombination of charge carriers and reduced device efficiency.…”
Section: Introductionmentioning
confidence: 99%